2011
DOI: 10.5114/wiitm.2011.26253
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing inguinal hernia repair with Lichtenstein technique using non-absorbable or partially absorbable mesh. Preliminary report.

Abstract: IntroductionThe Lichtenstein technique is currently considered the “gold standard” of open, anterior inguinal hernia repair. It is not free, however, of adverse effects, which may be caused by the implemented synthetic material.AimDetermination the influence of the mesh employed on treatment results including immediate complications, return to everyday activities, chronic pain occurrence and hernia recurrence.Material and methodsTension-free hernia repair using the Lichtenstein technique was performed in all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…A definition of CPIP was lacking in 31 (39%) of the studies (table 2) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. In the other 49 studies (61%), a total of 22 different definitions of CPIP were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A definition of CPIP was lacking in 31 (39%) of the studies (table 2) [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38]. In the other 49 studies (61%), a total of 22 different definitions of CPIP were identified.…”
Section: Resultsmentioning
confidence: 99%
“…However, among these studies, 33 different validated instruments were identified (tables 4, 5, 6) [11,13,14,17,19,21,26,28,29,32,36,38,41,43,45,47,48,51,53,56,57,58,59,60,61,62,63,64,65,79,90]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Bisgaard et al reported that in 67,306 primary hernia repairs there were 2,117 reoperations (3.1%) and 0.28% of original hernia repairs (187 cases) required re-reoperation, 5 indicating that if a repair fails once, it has a higher incidence of subsequent failure. Repair of recurrent hernias therefore needs a 'tailored' approach to reduce the rate of further recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…3 Pielaciski et al indicated that recurrences could occur owing to various causes such as age, body mass index (obesity), suture material, surgical technique, type of repair, length of surgery and previous hernia strangulation. 4 Bisgaard et al reported that in 67,306 primary hernia repairs there were 2,117 reoperations (3.1%) and 0.28% of original hernia repairs (187 cases) required re-reoperation, 5 indicating that if a repair fails once, it has a higher incidence of subsequent failure. Repair of recurrent hernias therefore needs a 'tailored' approach to reduce the rate of further recurrence.…”
Section: Discussionmentioning
confidence: 99%